High-dose siRNAs upregulate mouse Eri-1 at both transcription and posttranscription levels. - Yingnan Bian (Public Library of Science (PLoS), 2011)
The eri-1 gene encodes a 3' exonuclease that can negatively regulate RNA interference via siRNase activity. High-dose siRNAs (hd-siRNAs) can enhance Eri-1 expression, which in return degrade siRNAs and greatly reduces RNAi efficiency. Here we report that hd-siRNAs induce mouse Eri-1 (meri-1) expression through the recruitment of Sp1, Ets-1, and STAT3 to the meri-1 promoter and the formation of an Sp1-Ets-1-STAT3 complex. In addition, hd-siRNAs also abolish the 3' untranslated region (UTR) mediated posttranscriptional repression of meri-1. Our findings demonstrate the molecular mechanism underlying the upregulation of meri-1 by hd-siRNA.